Juridical Review Of Absolute Competency Of Tax Disputes Regarding Tax Assessment Letters (SKP) Issued By Officers Of The Directorate General Of Taxes (CASE STUDY ON DECISION No. 290/B/2019/PT.TUN.SBY) - Sitorus, Eduaward Tony; Letunggamu , Olfriady; Fitryantica , Agnes (Social Sciences Journal, 2024)
One way to increase and test the level of taxpayer compliance is by conducting a tax audit. The result of a tax audit is a Tax Assessment Letter (SKP). If you are not satisfied with the Tax Assessment Letter issued, the legal remedy that can be taken according to the Law on General Provisions and Tax Procedures is an objection and then an appeal to the Tax Court. In fact, some Taxpayers are suing the SKP to the State Administrative Court (PTUN) because the Tax Assessment Letter (SKP) fulfills the elements of a State Administrative Decision (KTUN) in accordance with the Government Administration Law so that it can be the object of a State Administrative Dispute (TUN). ). The purpose of this research is to add discourse or input to related parties if the Tax Assessment Letter (SKP) meets the requirements as KTUN and vice versa if the Tax Assessment Letter (SKP) cannot/is not the object of a lawsuit at the PTUN. However, the Tax Court is a special court from the TUN court. Apart from that, before a lawsuit is filed at the Administrative Court, the aggrieved party must first carry out administrative efforts in the form of objections and appeals in accordance with the Government Administration Law.